Microscale functional cytomics for studying hematologic cancers - Young, Edmond W. K. (American Society of Hematology, 2012)
An important problem in translational cancer research is our limited ability to functionally characterize behaviors of primary patient cancer cells and associated stromal cell types, and relate mechanistic understanding to therapy selection. Functional analyses of primary samples face at least 3 major challenges: limited availability of primary samples for testing, paucity of functional information extracted from samples, and lack of functional methods accessible to many researchers. We developed a microscale cell culture platform that overcomes these limitations, especially for hematologic cancers. A key feature of the platform is the ability to compartmentalize small populations of adherent and nonadherent cells in controlled microenvironments that can better reflect physiological conditions and enable cell-cell interaction studies. Custom image analysis was developed to measure cell viability and protein subcellular localizations in single cells to provide insights into heterogeneity of cellular responses. We validated our platform by assessing viability and nuclear translocations of NF-κB and STAT3 in multiple myeloma cells exposed to different conditions, including cocultured bone marrow stromal cells. We further assessed its utility by analyzing NF-κB activation in a primary chronic lymphocytic leukemia patient sample. Our platform can be applied to myriad biological questions, enabling high-content functional cytomics of primary hematologic malignancies.